MOTIVASI DAN ALASAN BERWIRAUSAHA: STUDI KASUS WIRAUSAHAWAN MUDA DI SUMATERA UTARA - Hammuda Sitorus; Asmar Yulastri; Henny Yustisia; Yudha Aditya Fiandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and analyze the main motivations and reasons people choose entrepreneurship, particularly in the context of young entrepreneurs in North Sumatra. This research uses a qualitative approach with a case study method through direct observation and in-depth interviews. The results show that entrepreneurial motivation stems from internal and external factors that interact with each other, including economic pressures, family responsibilities, spiritual values, the desire for independence, opportunity exploitation, and social concern. These findings are reinforced by entrepreneurial motivation theories that emphasize the role of push and pull factors in the decision to start a business. This research is expected to contribute to the development of entrepreneurship education in higher education and serve as a reference for prospective young Indonesian entrepreneurs.